Mediatized Catholicism—Minority Voices and Religious Authority in the Digital Sphere - Alberta Giorgi (Religions, 2019)
Over the last decade, many scholars have explored the thesis of the mediatization of religion proposed by Hjarvard and how mediatization has impacted religious authority. While some scholars have underlined the increasing opportunities for marginalized religious actors to make their voices heard, others have explored how mediatization can also result in the enhancement of traditional religious authority or change the logic of religious authority. Against this background, in this paper, I focus on Christian LGBT+ digital voices in Italy to explore how they discursively engage with the official religious authority of the Catholic Church. The analysis adopts Campbell typology of religious authority. It highlights the complex balance between challenging and reaffirming traditional religious authority, and points out the role of the type of digital community in exploring the effects of the mediatization of religion.